Strategi Pengelolaan Beban Kerja dalam Meningkatkan Komitmen SDM di Lingkungan Kerja Startup Digital di Kelurahan Bugangan Semarang - Bonaventura Hendrawan Maranata; Dian Prasetyo Widyaningtyas; Tan, Marcella Wijaya; Andini Galih Ayu Puspitasari (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
The rapid growth of digital startup companies in Indonesia brings its own challenges in human resource (HR) management, especially related to workload and organizational commitment. High work dynamics, aggressive targets, and intense operational pressure can cause an imbalance in workload that impacts motivation, work stress, and increased turnover intention. HR commitment is a key factor in startup success, but it is difficult to achieve without effective and humane workload management. This community service activity was carried out by Karangturi National University (UNKARTUR), through the Faculty of Economics, Business and Humanities (FEBHum), which aims to improve the understanding, skills, and awareness of digital startup entrepreneurs and employees in Bugangan Village, Semarang, regarding workload management strategies. The methods used include workshops, group discussions, and direct assistance. The results of the activity showed an increase in participants' understanding of the impact of disproportionate workloads, as well as the ability to implement efficient and sustainable work strategies. This activity also encourages collaboration between academics and practitioners in designing a healthy and adaptive work environment. With better workload management, it is hoped that the level of commitment, satisfaction, and retention of employees in digital startups can increase, while strengthening the competitiveness of local businesses in the era of digital transformation.